Crystal storage and transfer in basaltic systems: The skuggafjöll eruption, Iceland - Neave, DA; Maclennan, J; Hartley, ME; Edmonds, M; Thordarson, T (Oxford University Press (OUP), 2014)
Magma mixing and crystal mush disaggregation are important processes in basaltic magma reservoirs. We carried out a detailed petrological and geochemical study on a highly plagioclase-phyric eruption within the Eastern Volcanic Zone of Iceland – the Skuggafjöll eruption – in order to investigate crystal storage and transport processes within a single magmatic system. Crystal content and phase proportions vary between samples: the least phyric samples have phase proportions similar to the low pressure, 3-phase gabbro eutectic (plg:cpx:ol ~ 11:6:3), whereas highly phyric samples are strongly enriched in plagioclase (plg:cpx:ol ~ 8:1:1). Statistically significant geochemical variability in 28 whole-rock samples collected across the eruption can be accounted for by variable accumulation of a troctolitic assemblage containing plagioclase and olivine in an approximately 9:1 ratio. Two macrocryst assemblages are defined using compositional and textural information recorded in QEMSCAN® images: a primitive assemblage of high-anorthite plagioclase (An>83) and high-forsterite olivine (Fo>84), and an evolved assemblage of low-anorthite plagioclase (An<79), low forsterite olivine (Fo<82) and clinopyroxene (Mg# ~ 82). Plagioclase and olivine have strongly bimodal composition distributions whereas the composition distribution of clinopyroxene is unimodal. The mean trace element composition of melt inclusions hosted within high-forsterite olivine and high-anorthite plagioclase macrocrysts is the same (mean Ce/Y ~ 0.47–0.48), confirming that both primitive macrocryst phases crystallised from the same distribution of melts. Clinopyroxene macrocrysts and matrix glasses are in Ce/Yb equilibrium with each other, indicating that the evolved assemblage crystallised from melts with a more incompatible trace element-enriched composition (mean Ce/Y ~ 0.65–71) than the primitive assemblage. Variability in whole-rock, macrocryst and melt inclusion compositions suggests that the Skuggafjöll magma experienced two stages of ...